The Effectiveness of The Implementation of The Community-Based Total Sanitation Program, The First Pillar of Stop Open Defecation in The Work Area of The Palmerah District Community Health Center in 2022 - Nurhayati, Rizka; Angeliana Kusumaningtiar, Devi; Handayani, Putri; Wadjir Sangadji, Namira (Jurnal KESANS : Kesehatan dan Sains, 2023)
Introduction: The condition of latrines in West Jakarta Administrative City includes the number of permanent healthy latrines 69%, semi-permanent healthy latrines 8%, communal latrines 18% and households that still defecate openly in a closed manner (have toilets but do not have advanced waste treatment) reaches 5%, while for regional data the highest Open Defecation Free (ODF) sub-district status is in Kembangan and Tambora Subdistricts,  each of which already has 3 ODF Sub-Districts and areas that do not yet have ODF Sub-Districts namely Cengkareng and Palmerah Subdistricts. Objective: This study aims to determine the Effectiveness of the Implementation of the Community-Based Total Sanitation Program First Pillar Stop Open Defecation in the working area of ??the Palmerah District Health Center, West Jakarta Administrative City in 2022. Method: This type of research is descriptive qualitative with a phenomenological design. Result and Discussion: The results of the study obtained a gap in the First Pillar CBTS program to Stop Open Defecation, including in the planning variable, it was found that there were no sanitarians who were trained to become CBTS facilitators, in the implementation variable the result was that the triggering implementation was not optimal by not carrying out the triggering stages according to the requirements,  then in the monitoring and control variables, it was found that residents had open defecation and had not applied sanctions or awards related to the first pillar CBTS implementation of Stop Open Defecation.  Conclusion: Planning for the CBTS Pillar 1 Stop Open Defecation program at the Palmerah District Public Health Centre for the Planning Process is appropriate, but for human resources, it is still necessary to increase competence in the form of trainings as an effort to support the smooth implementation of the CBTS program